2019
DOI: 10.7717/peerj.8003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phylogenetic analysis of Chinese sacbrood virus isolates fromApis mellifera

Abstract: BackgroundSacbrood virus (SBV) is one of the most pathogenic honeybee viruses that exhibits host specificity and regional variations. The SBV strains that infect the Chinese honeybee Apis cerana are called Chinese SBVs (CSBVs).MethodsIn this study, a CSBV strain named AmCSBV-SDLY-2016 (GenBank accession No. ) infecting A. mellifera was identified by electron microscopy, its protein composition was analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis and agar gel immunodiffusion assay, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(70 reference statements)
2
7
0
Order By: Relevance
“…The detection of AcSBV prevalence in A. mellifera populations from the sampling sites where A. cerana and A. mellifera were crossbreeding confirmed that AcSBV prevalence rates gradually developed a similar trend in the A. cerana and A. mellifera crossbreeding apiaries, and the existence of AcSBV cross-infection between A. cerana and A. mellifera was also confirmed by phylogenetic analysis based on partial VP1 sequences [33]. Similar to our case, some SBV strains from A. mellifera included in this study were found to be distinct from other AmSBV strains in terms of genomic features and were clustered with AcSBVs based on whole genome comparisons and phylogenetic analysis [24,30,36,40]. Strains from the same or closer geography distance showed higher similarity, and the phylogenetic analysis also indicated the same result [24,30,36,40,44].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The detection of AcSBV prevalence in A. mellifera populations from the sampling sites where A. cerana and A. mellifera were crossbreeding confirmed that AcSBV prevalence rates gradually developed a similar trend in the A. cerana and A. mellifera crossbreeding apiaries, and the existence of AcSBV cross-infection between A. cerana and A. mellifera was also confirmed by phylogenetic analysis based on partial VP1 sequences [33]. Similar to our case, some SBV strains from A. mellifera included in this study were found to be distinct from other AmSBV strains in terms of genomic features and were clustered with AcSBVs based on whole genome comparisons and phylogenetic analysis [24,30,36,40]. Strains from the same or closer geography distance showed higher similarity, and the phylogenetic analysis also indicated the same result [24,30,36,40,44].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our case, some SBV strains from A. mellifera included in this study were found to be distinct from other AmSBV strains in terms of genomic features and were clustered with AcSBVs based on whole genome comparisons and phylogenetic analysis [24,30,36,40]. Strains from the same or closer geography distance showed higher similarity, and the phylogenetic analysis also indicated the same result [24,30,36,40,44]. Indeed, it was shown that the cross-infection of SBV strains occurs between two honeybee species in other countries, including China, Vietnam, and Korea, leading to the high genetic divergence among SBV strains [24,30,36,40].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations